Numerical simulation of collision between two droplets in the T-shaped microchannel with lattice Boltzmann method - Arshia Merdasi; Saman Ebrahimi; Ali Moosavi; Mohammad Behshad Shafii; Farshad Kowsary (AIP Advances, 2016)
In this study, the Lattice Boltzmann Method (LBM) is used to investigate the deformation of two droplets within microfluidic T-junctions (MFTD). In order to increase the accuracy the two immiscible fluids are modeled using the He-Chen-Zhang model. First, this model is applied to ensure that the surface tension effect existing between the droplets and the continuous fluid is properly implemented in the model. Then the collision and merging of the two droplets within the intersection of a T-shaped microchannel is investigated. For generating droplet formation the effects of relevant dimensionless parameters such as the Reynolds, the Weber numbers as well as a collision parameter affecting the two droplets during their motion and deformation are studied. It is found that by increasing the relative velocities of the inlet flows and droplet sizes, the deformation of the two droplets increases significantly. Our results also show that when the surface tension increases, it takes less time for the droplets to collide each other. Therefore, the droplet formation in MFTD depends significantly on the droplet size, inlet velocity as well as surface tension. Finally, we successfully investigated a two-phase flow streaming energy conversion system associated with droplet coalescence. The apprehension of fundamental physics of the droplet formation is useful for many applications including, stem cell phenotypes, cell transplantation and drug delivery in biomedical applications.